Ferramenta computacional para simulação de aeronaves rádio controladas - Bonote, Matheus Nogueira (2023)
This work shows the development of an innovative computational tool for UAV (Unmanned Aerial Vehicle) flight simulation and its application to Aerodesign competitions from SAE. In Brazil, the Aerodesign competition from SAE is an annual event that gathers engineering students from all over the country, challenging them to design, build and operate radiocontrolled aircrafts. With the goal of providing the competitors a tool that helps them in ther development and improving processes, it was developed a computational tool that allows them to simulate UAV flights. The tool developed offers features like mission planning, path defining, tridimensional visualization of the flight environment and performance and stability analysis of the aircraft. These features can be adapted and applied in the Aerodesign context, allowing teams to simulate the behavior of the aircraft in different states and conditions of flight. Using the UAV simulation tool, Aerodesign teams may evalue the aerodinamical efficiency of their projects, make ajustsments and optimizations, in addition to analyzing the stabily and performance of the aircraft in different manouvers. This allows the refinement of the project before the physical construction of the aircraft, saving resources and increasing chances of a competitive performance. In addition, the tool also allows analysis of risks and the identification of possible safety problems on the aircraft. This way, teams can act preventively and adopt safer flight strategies, assuring the aircraft integrity and safety of those present. Therefore, the application of this UAV flight simulation tool on the Aerodesign competition from SAE provides an innovative and effitient approach on developing and optimizing the aircrafts designed by the teams. This tool contributes to improving performance, safety and competitivety of the aircrafts in the competition, providing significant progress in Aerodesign.